Process simulation for revamping of a dehydration gas plant - H.A. El Mawgoud; T.M. Elshiekh; S.A. Khalil (Egyptian Journal of Petroleum)
Natural gas is an important energy source among other sources of fossil fuels. It is usually produced saturated with water vapor under production conditions. The dehydration of natural gas is very important in the gas processing industry to remove water vapor present in the gas stream which may cause hydrate formation at low-temperature conditions that may plug the system. The most common practice to remove water from natural gas streams is to use TEG (triethylene glycol) in the gas dehydration process. This paper focuses on modeling and simulation for revamping a dehydration gas plant named “Akik” existing in Egypt and owned by Khalda Petroleum Company. The plant was almost depreciated, and the company administration decided to revamp it and at the same time perform the necessary modifications in order to cut down the equipment cost and reduce energy consumption. To achieve this target the existing plant configuration was simulated using Aspen HYSIS program. The model has been built according to the actual process flow diagram. The results of this model could be considered as a basis on which a new heat and material balance will be developed for the plant. Three different alternatives were investigated and evaluated to choose the optimum one with respect to the minimum equipment cost, provided keeping the same specifications and quantity of the produced gas.